Lisdexamfetamine reduces the compulsive and perseverative behaviour of binge-eating rats in a novel food reward/punished responding conflict model - Heal, David J; Goddard, Simon; Brammer, Richard J; Hutson, Peter H; Vickers, Steven P (Journal of psychopharmacology (Oxford), 2016)
Compulsive and perseverative behaviour in binge-eating, female, Wistar rats was investigated in a novel food reward/punished responding conflict model. Rats were trained to perform the conditioned avoidance response task. When proficient, the paradigm was altered to a food-associated conflict test by placing a chocolate-filled jar (empty jar for controls) in one compartment of the shuttle box. Entry into the compartment with the jar triggered the conditioning stimulus after a variable interval, and foot-shock 10 seconds later if the rat did not leave. Residence in the ‘safe’ compartment with no jar did not initiate trials or foot-shocks. By frequently entering the chocolate-paired compartment, binge-eating rats completed their 10 trials more quickly than non-binge controls. Binge-eating rats spent a greater percentage of the session in the chocolate-paired compartment, received foot-shocks more frequently, and tolerated foot-shocks for longer periods; all consistent with compulsive and perseverative behaviour. The d-amphetamine prodrug, lisdexamfetamine, has recently received US approval for the treatment of moderate to severe binge-eating disorder in adults. Lisdexamfetamine (0.8 mg/kg po [d-amphetamine base]) decreased chocolate consumption by binge-eating rats by 55% and markedly reduced compulsive and perseverative responding in the model. These findings complement clinical results showing lisdexamfetamine reduced compulsiveness scores in subjects with binge-eating disorder.